ENKAPSULASI EKSTRAK KULIT BUAH DELIMA (PUNICA GRANATUM L.) DALAM NANOSTRUCTURED LIPID CARRIER (NLC) UNTUK MENINGKATKAN AKTIVITAS INHIBITOR TIROSINASE SECARA IN VITRO - Nadya Alifia, Annisa
Hyperpigmentation is a skin condition when patches appear darker in color than the surrounding normal skin caused by excess melanin production. To overcome this, it has been investigated that pomegranate peel extract (Punica granatum L.) has an important role in inactivating the activity of the tyrosinase enzyme in the process of melanogenesis. To increase its activity, pomegranate peel extract (EKD) is encapsulated in a Nanostructured Lipid Carrier (NLC). This study aims to increase the activity of the formulated EKD. The NLC-EKD formulation was prepared by screening pair surfactant and their concentration comparisons to determine the type of used surfactant. The process and formulation optimization was perfomed. Preparation of NLC-EKD was used melt-emulsification and ultrasonication methods. The best NLC-EKD formulation with the composition of glyceryl monostearate of 4.8% (w/v), olive oil of 3.2% (w/v), colliphor RH40 of 3% (w/v), PEG 400 of 3% (b/v), EKD of 0.012% (w/v), and aquadest of 85.988% (w/v). The organoleptic characteristics of NLC-EKD were milky white color and odorless, particle size of 126.07 ± 5.32 nm, polydispersity index of 0.356 ± 0.063, zeta potential of - 38.58 ± 3.74 mV, encapsulation efficiency of 86.27 ± 0, 46% and pH of 5.62 ± 0.19. The NLC-EKD formulation can increase the effectiveness of EKD as a tyrosinase inhibitor with IC50 EKD values of 8289.90 ± 460.42 ppm and NLC-EKD of 241.05 ± 49.48 ppm, where the IC50 value of NLC-EKD experienced a significant increase (p < 0.05) is 33 in comparison with IC50 EKD value. Stability data showed that the particles size of NLC-EKD was increased at 4, 25, and 40°C for 28 days.